Genetic and environmental (physical fitness and sedentary activity) interaction effects on cardiometabolic risk factors in Mexican American children and adolescents. Issue 4 (20th February 2018) - Arya, Rector; Farook, Vidya S.; Fowler, Sharon P.; Puppala, Sobha; Chittoor, Geetha; Resendez, Roy G.; Mummidi, Srinivas; Vanamala, Jairam; Almasy, Laura; Curran, Joanne E.; Comuzzie, Anthony G.; Lehman, Donna M.; et al.
ABSTRACT: Knowledge on genetic and environmental (G × E) interaction effects on cardiometabolic risk factors (CMRFs) in children is limited. The purpose of this study was to examine the impact of G × E interaction effects on CMRFs in Mexican American (MA) children ( n = 617, ages 6–17 years). The environments examined were sedentary activity (SA), assessed by recalls from "yesterday" (SAy) and "usually" (SAu) and physical fitness (PF) assessed by Harvard PF scores (HPFS). CMRF data included body mass index (BMI), waist circumference (WC), fat mass (FM), fasting insulin (FI), homeostasis model of assessment—insulin resistance (HOMA‐IR), high‐density lipoprotein cholesterol (HDL‐C), triglycerides (TG), systolic (SBP) and diastolic (DBP) blood pressure, and number of metabolic syndrome components (MSC). We examined potential G × E interaction in the phenotypic expression of CMRFs using variance component models and likelihood‐based statistical inference. Significant G × SA interactions were identified for six CMRFs: BMI, WC, FI, HOMA‐IR, MSC, and HDL, and significant G × HPFS interactions were observed for four CMRFs: BMI, WC, FM, and HOMA‐IR. However, after correcting for multiple hypothesis testing, only WC × SAy, FM × SAy, and FI × SAu interactions became marginally significant. After correcting for multiple testing, most of CMRFs exhibited significant G × E interactions (Reduced G × E model vs. Constrained model). These findings provide evidence that genetic factors interact with SA and PF to influence variation in CMRFs, and underscore the need for better understanding of these relationships to develop strategies and interventions to effectively reduce or prevent cardiometabolic risk in children.